Insight into the stereoelectronic parameters of N-triphos ligands via coordination to tungsten(0). Issue 13 (25th February 2016) - Phanopoulos, Andreas; White, Andrew J. P.; Long, Nicholas J.; Miller, Philip W.
Abstract : A series of new N-triphos tungsten complexes have been synthesised and structurally characterised. Abstract : A series of new N-triphos tungsten complexes have been synthesised and structurally characterised. The coordination behaviour of a range of N-triphos (N(CH2 PR2 )3, NP3 R ) ligands, and a mixed-arm diphosphine-pyridyl (PPN Cyh ) ligand were explored. The steric and electronic parameters of five N-triphos ligands: NP3 Ph, NP3 iPr, NP3 Cyp, NP3 Cyh and NP3 PhF2, and the carbon-centred triphos ligand, CH3 C(CH2 PPh2 )3 (MeCP3 Ph ), were established. Steric parameters were evaluated by analysing the cone angles calculated from X-ray crystal structures, whilst the electron-donating ability of the ligands was determined from 31 P– 77 Se NMR coupling constants of selenium derivatives and the IR carbonyl stretching frequencies across a series of tungsten–carbonyl complexes. In general, electron-rich phosphines formed bidentate complexes while less electron-rich ligands coordinated in a tridentate mode, regardless of steric bulk. An indirect interaction between the apical nitrogen of the ligand and metal centre is implicated for tridentate complexes and is supported through DFT calculations and analysis of N-protonated complexes. Complexes1, 3, 4, 6–8 and10 were characterised by single-crystal X-ray crystallography.